Exploring the Causes of Job Burnout Among Academic Leaders at Saudi Higher Educational Institutions - Alenazy, Hanan Muhaya (Journal of Posthumanism, 2025)
This qualitative study examines the internal and external factors that influence job burnout among higher-education academics within the peculiar sociocultural and institutional environment of Saudi Arabia. Although “burnout” is a well-established subject of enquiry, its contributing factors remain underexplored in the Saudi context. Participants were recruited from five Saudi state universities using purposive snowball sampling; a diverse sample allowed for the inclusion of academics with different expertise and experiences. On-site or telephonic semi-structured interviews (lasting between 2 and 2.5 hours to minimize participant fatigue) further enriched data collection. These interviews were audio-recorded, transcribed, and subjected to thematic analysis to identify common patterns and themes. Based on the job demands–resources theory, Maslach’s three-dimensional model (emotional exhaustion, depersonalization, and diminished personal accomplishment), and data analyses, the findings provided new knowledge about how the interaction of culture, institution, and personal factors contributes to burnout. The study recommends culturally sensitive interventions to reduce burnout and improve well-being among academics. By framing these results in the context of Saudi Arabia’s fast-changing higher-education sector, these findings add to the corpus of literature on burnout.